Sensory Integration - the weight of stimuli. The role of parents - Maj-Gnat, Katarzyna; De Pourbaix, Renata; Stępnik, Jolanta; Wołoszynek, Eliza; Kielar, Maciej (Journal of Education, Health and Sport, 2019)
INTRODUCTION Sensory integration is a kind of integration or organization of stimuli, the ability to feel and respond properly to news from the world. The organization of stimuli takes place in the brain so that later can use them to create appropriate reactions and behaviors. If the flow of stimuli is disturbed then some reactions, the body’s response may be incorrect. OBJECTIVE The purpose of this article is to present in a understandable way the sensory integration process and the impact of various stimuli on its condition. It also shows how important parents play in the development and therapy of children with sensory integration disorders. THE WEIGHT OF THE BODCIES The stimuli is food that absorbs our brain through every organ of our body. We are what we eat, that is why, it is so important what we feed our children’s brain. Impulses reach the body thanks to the senses: sight, hearing, taste, smell, touch and proprioceptive, atrial and interoceptive. SUMMARY Sensory integration is the whole of reactions that take place between the outside world and our body. The most important and the most intense time of physical and mental development is childhood during which we provide our body with the most stimuli. For children with sensory integration disorders and without these disorders, the best therapists are parents.